Ethnocentrism and Its Effects as Depicted in The Kite Runner Novel (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
This study analyzed the portrayal of ethnocentrism and its negative effects in Khaled Hosseini’s The Kite Runner using Bizumic’s ethnocentrism theory. This study used descriptive qualitative methods; the data were collected from the novel in monologues, dialogues, and narratives. Based on the data, ethnocentrism depicted in the novel taking setting in Afghanistan was represented in terms of superiority and in-group preference. The novel depicted that one ethnic, the Pashtun, felt more superior to the Hazara. This superiority made the Pashtun always evaluate other groups based on their standard. They built the in-group preference in which they regard their standard as the best compared to the Hazara. In addition, the negative effects of ethnocentrism were manifested into three points: violence against other groups, ethnic wars, and desire to control the territory. In short, ethnocentrism causes differences in thoughts and opinions between one group and another and further affects their relationship negatively.